Assessing glomerular filtration rate in patients with severe heart failure: comparison between creatinine-based formulas - Libório, Alexandre; Uchoa, Russian; Neto, João; Valdivia, Juan; Daher, Elizabeth De Francesco; Mejia, Juan (São Paulo Medical Journal, 2012)
CONTEXT AND OBJECTIVE: Severe heart failure is highly associated with chronic kidney disease (CKD). Serum creatinine is a poor indicator of renal function and glomerular filtration rate (GFR) estimation is an accessible method for assessing renal function. The most popular formulas for GFR estimation are the Cockcroft-Gault (CG), the four-variable Simplified Modification of Diet in Renal Disease (sMDRD) and the recently introduced CKD-Epidemiology Collaboration (CKD-EPI). The objective of the study was to analyze the correlation between these three equations for estimating GFR in patients with severe heart failure. DESIGN AND SETTING: Cross-sectional observational study at a university reference center. METHODS: GFR was estimated in patients with severe heart failure who were awaiting heart transplantation, using the CG, sMDRD and CKD-EPI formulas. These estimates were analyzed using Pearson’s correlation and Bland-Altman analysis. RESULTS: This study included 157 patients, of whom 32 (20.3%) were female. Normal serum creatinine concentration was observed in 21.6%. The mean GFR according to CG, sMDRD and CKD-EPI was 70.1 ± 29.5, 70.7 ± 37.5 and 73.7 ± 30.1 ml/min/1.73 m2 ; P ≥ 0.05. Pearson’s coefficient demonstrated good correlations between all the formulas, as did Bland-Altman. However, the patients presented GFR < 60 ml/ min more frequently with the sMDRD formula (54.1% versus 40.2% for CG and 43.2% for CKD-EPI; P = 0.02). CONCLUSION: Despite the good correlation and agreement between the three methods, the sMDRD formula classified more patients as presenting GFR less than 60 ml/min.